Evaluasi Implementasi Radiology Information System Picture Archiving and Communication System (RISPACS) dengan Pendekatan Model HOT-FIT - Suandari, Putu Vierda Lya; Adi, Kusworo; Suryawati, Chriswardani (Universitas Diponegoro, 2019)
The application of current technology such as the Radiology Information System Picture Archiving and Communication System (RISPACS) in radiology that doesn’t meet the user’s expectation can raise the inconvenience and affect their productivity. To anticipate this, it is important to understand the basic factors that contribute to the reception and successfulness of applicating RISPACS. This study aims to describe the evaluation of the successful implementation of RISPACS using the Human Organization Technology (HOT FIT) model approach in Radiology Installation at Sanglah Hospital Denpasar. The data in this research were analyzed by Partial Least Square (PLS) test and measuring 71 radiologists as respondents who use RISPACS. The evaluation results of the Human Organization Technology (HOT FIT) model show that the successful implementation of RISPACS technology has a positive assessment that is seen from the user's attitude in responding to a RISPACS technology that is felt to be in accordance with the expectations and operational needs of the user. Variable of system quality, information quality, service quality have a positive influence on system user variable and user satisfaction. While the variable of system users, user satisfaction, organizational structure, and organizational environment had a positive and significant effect by the t-statistic value of >1,96.